Controlled trial of long term oral potassium supplements in patients with mild hypertension. Issue 6585 (6th June 1987) - Siani, A; Strazzullo, P; Russo, L; Guglielmi, S; Iacoviello, L; Ferrara, L A; Mancini, M
Abstract : A 15 week randomised double blind placebo controlled trial of oral potassium supplements (48 mmol daily) was conducted in 37 patients who had mildly increased blood pressure and a normal dietary intake of sodium. After a two month run in and a one week baseline period the patients were randomly assigned to receive either potassium supplements (n = 18) or placebo (n = 19). By the third week of treatment blood pressure in the actively treated group had decreased significantly compared with that in the placebo group, though the decrease reached its maximum after 15 weeks. Urinary potassium excretion increased significantly in the group who received potassium supplements, but no significant changes were found in plasma sodium and potassium concentrations or in urinary sodium excretion. In a subgroup of 13 patients who underwent a further nine weeks of treatment with oral potassium supplements at half of the previous dose (24 mmol daily) their blood pressure, at the end of this second study period, was still significantly lower compared with their baseline value but not with that of the placebo group. These results show that moderate oral potassium supplements are associated with a long term reduction in blood pressure in patients who have mild hypertension.